Thermal and Acidic Treatments of Gluten Epitopes Affect Their Recognition by HLA-DQ2 in silico - Gao, Jihui; Du, Haolan; Zhou, Zekun; Liang, Zhongxin; Liang, Hongrui; Zhang, PeiAo; Wei, Xue; Liu, Shujun; Fu, Linglin; Wang, Yanbo; Che, Huilian; Xue, Wentong; et al. (Frontiers in Nutrition, 2021)
Celiac disease (CD) is a prevalent disorder with autoimmune features. Dietary exposure of wheat gluten (including gliadins and glutenins) to the small intestine activates the gluten-reactive CD4+ T cells and controls the disease development. While the human leukocyte antigen (HLA) is the single most important genetic factor of this polygenic disorder, HLA-DQ2 recognition of gluten is the major biological step among patients with CD. Gluten epitopes are often rich in Pro and share similar primary sequences. Here, we simulated the solution structures changes of a variety of gluten epitopes under different pH and temperatures, to mimic the fermentation and baking/cooking processes. Based on the crystal structure of HLA-DQ2, binding of differently processed gluten epitopes to DQ2 was studied in silico. This study revealed that heating and pH change during the fermentation process impact the solution structure of gluten epitope. However, binding of differently treated gluten epitope peptide (GEP) to HLA-DQ2 mainly depended on its primary amino acid sequence, especially acidic amino acid residues that play a pivotal role in their recognition by HLA-DQ2.